Peran Komunikasi Interpersonal dalam Membangun Harmoni dan Produktivitas Kerja di Univeristas Selamat Sri - Siti Rohmah; Novia Sri Falinda (LPPM UNISDA, 2026)
Interpersonal communication plays a crucial role in creating a harmonious work environment, particularly in educational institutions. At Selamat Sri University, effective interactions between faculty and students can influence organizational dynamics and learning outcomes. This study aims to explore the role of interpersonal communication in building harmony and work productivity at Selamat Sri University. The research method used was a qualitative approach with in-depth interviews and participant observation. The results showed that open and empathetic communication improves interpersonal relationships, reduces conflict, and encourages better collaboration. Furthermore, good interpersonal communication contributes to increased motivation and job satisfaction. These findings indicate that developing interpersonal communication skills in a university environment can be an important strategy in improving harmony and work productivity.